Dietary Linoleic Acid Targets Skeletal Muscle to Impact Energy Metabolism (P08-124-19). (24th October 2019) - Snoke, Deena; Hsuan-Hsiao, Yung; Cole, Rachel; Pedersen, Theresa; Newman, John; Borkowski, Kamil; Banh, Taylor; Angelotti, Austin; Schnell, Patrick; Belury, Martha
Abstract: Objectives: Investigate the impact of dietary linoleic acid (LA) on whole-body energy metabolism, fatty acid uptake, oxylipin metabolites, and energy production machinery in skeletal muscle. Methods: Mice were fed modified AIN-93 M diets containing 6% wt of LA or palmitic acid (PA) for 5 weeks. To address energy balance, grip strength, blood glucose, and body composition were measured weekly and indirect calorimetry was performed after 4.5 weeks of diet. To address skeletal muscle architecture, cross-sectional area was quantified in quadriceps. To determine the effect of LA diet on skeletal muscle lipids, fatty acid composition was measured in quadriceps using GC. Targeted lipidomics using LC-MS/MS was utilized to measure LA-derived oxylipins in mitochondria isolated from gastrocnemius. Results: No difference in food intake, body weight, blood glucose, or body composition were observed between diet groups. Mice fed the LA diet exhibited higher heat production and lower respiratory exchange ratio, independent of ambulatory activity compared to mice fed the PA diet. Cross sectional area analysis in quadriceps muscle revealed that mice fed the LA diet had smaller muscle fibers compared to mice fed the PA diet. The LA diet increased LA level in quadriceps. Using hierarchal cluster analysis, we identified several unique patterns of oxylipins that impact insulin sensitivity and may be associated with increased mitochondrial capacity. Mice fed the LA diet exhibited a three-fold increase of oxylipin metabolites 9- and 13-HODE, and 12, 13-diHOME. Conclusions: Mice fed a diet fortified in LA have increased LA in skeletal muscle, changes to skeletal muscle architecture, favorable changes to whole body energy metabolism, and increases in LA-derived oxylipins in skeletal muscle mitochondria. Our discovery that LA generates 9-HODE and 13-HODE in muscle mitochondria suggests that downstream pathways, including PPARg transactivation, may be linked with effects on muscle energy metabolism. Funding Sources: Funding was provided by the National Institutes of Health (NIH) R21CA185140, Ohio Agriculture Research and Development Center and the Carol S. Kennedy Professorship. DBS is supported by the Center for Muscle Health and Neuromuscular Disorders Predoctoral Research Fellowship.